Qualidade da água por indicadores ambientais e análise da resistência de E. coli isoladas em águas superficiais urbanas - Malagi , Ivair (2018)
The aquatic ecosystems of urban rivers are affected by the disposal of waste from the sewage network. In the present research, the water quality of six rivers of the city of Cascavel - PR, being the rivers Cascavel, Quati, Bezerra, Antas, Lageado Clarito and Amambay. The collections conducted from March to November 2017 were used microbiological, physico-chemical and susceptibility/resistance of strains of Escherichia coli to antimicrobials. For coliforms it was followed the methodology described by Silva et al. (1997), the physical-chemical parameters performed with the Horiba manual probe end the susceptibility antimicrobial was evaluate accoording with the recomendations of Clinical and Laboratory Standards Institute (2015). There were significant differences between the months evaluated for the physico-chemical, microbiological and resistance parameters. Among the parameters evaluated just oxygen dissolved, solid total and biochemical oxygen demand, don't were significant. All the six rivers evaluated exceed the limit (<10MNP/mL) for coliforms thermotolerant. Was observed that 55.5% of strains of Escherichia coli were resistent at least one antimicrobial and 14.4% presented multiresistence. The major resistances were to ampicillin, amoxicillin and tetracycline with 21.1, 16.6 and 20% respectively. The result of this search contributing for an evaluation of caution associated with contamination of the waters by sewage, with bacterias highly resistant to antimicrobial on the urban center rivers.